Active, Passive and Apathetic: Imaginary of the Costa Rican Population on Politics and Democracy - Díaz González, José (2014)
This paper proposes a classification of Politics and Democracy in Costa Rica according to societal opinions, based on a survey conducted to collect data. Then, a cluster analysis (k-means) was conducted. In order to understand the different behaviors of the population in relation to the political sphere, a classification of research participants was developed.